ANALYSIS OF THE DEMAND FOR MONEY AND THE VELOCITY OF MONEY IN THE DIGITAL ECONOMY ERA: A CASE STUDY IN INDONESIA - Hari Setia Putra; Mutia Huljannah; Monica Putri (Riset Ekonomi Pembangunan, 2021)
In the digital economy era, efficiency and effectiveness are required in carrying out all life activities, including transaction activities. The urge to payment innovates systems as an effort to meet the needs of the community has led to several new non-cash-based payment instruments, such as paperless-based payment transactions. The existence of non-cash transactions shifts the role of cash in society. This study aims to examine the effect of paperless-based non-cash payments represented by credit cards, debit cards, and electronic money on the demand and velocity of money in Indonesia. Using monthly data sourced from Bank Indonesia and the Central Statistics Agency for the period 2010M1-2019M11. The right analysis used to see the effect of payment system innovation on-demand and velocity of money circulation is the Error Correction Model. The findings in the literature state that there is a significant effect of paperless-based payments as a form of payment system innovation on the demand and velocity of money circulation in Indonesia. The strong influence between the demand for money and the velocity of money with paperless-based non-cash transactions in Indonesia in the long term indicates that policymakers need to be careful in making decisions. The long-term relationship explains that the central bank can influence people's transaction behavior. Given that currency in circulation forms a significant part of a central bank's balance sheet, the shrinking demand for currency will have important implications on the central bank's seigniorage income, its independence, and its ability to conduct monetary policy. Thus, it is important to check and understand the trend of money demand and the velocity of money so that it can provide long-term profits.